A GIS-based automated procedure to assess disused areas: Identification methods and regeneration opportunities - Francini, Mauro; Margiotta, Nicole; Palermo, Annunziata; Viapiana, Maria Francesca (TeMA - Journal of Land Use, Mobility and Environment, 2020)
Regeneration of disused sites represents a significant opportunity. The scientific interest in their redevelopment possibilities has grown considerably in recent years. Despite this, a shared definition of disused sites which goes beyond that of brownfields and allows recognition the size of the problem on a transnational scale is still lacking. This study provides an overview of the main definitions provided by scientific literature and on this basis, it proposes a parametric definition of functionally disused areas. Subsequently, a GIS-based operational tool able to map functionally disused areas through a progressive screening of the local territory is introduced. The proposed methodology is tested on two Italian municipalities. It is the first step of a research aimed at defining a wider process able to assess the possibility of converting disused areas into multifunctional or monofunctional “smart” districts. They could be, indeed, characterized by a mixed use – contributing to soil consumption reduction – or by a single use – “social infrastructures” – linked to the needs that emerged as result of Covid 19 pandemic. This assessment process, hence, could support urban planning both at ordinary and emergency phase, allowing to identify in very short time areas where temporary facilities could be installed.